GAMBARAN KESEHATAN WARGA KOTA JAKARTA DI LINGKUNGAN PADAT PENDUDUK - Hazel Aprilia Hutabarat; Litha Sari Arfina Pane; Vallerie Meijer; Dewina Ayundita; R. Ghasa Marjani; Bonar Hutapea (Jurnal Psikohumanika, 2017)
The growth of urban population has become an important concern, especially about the risks of physical and mental health among the urban people. Like the other big cities, Jakarta’s population has also increasing rapidly. Unfortunatelly, the growing number of people isuneventlydistributed, which cause densely housing areas to emerge. This study is aim to observe physical and mental health among urban people who lived in densely populated area. This study used qualitative method through in-depth interview with two middle-age woman as the subjects. Subjects explained that they keep themselves healthy by regularly participated on government health check programs. They used public health facilities and services, such as BPJS and Puskesmas, and found them helpful. In addition, theydeveloped good relationship within other resident in the neighborhood and gave psychological support to each other which lighten their mental burden living in the city.